As an inhibitor of norepinephrine release, dexmedetomidine provides no improvement on stroke-associated pneumonia in mice - Zhou, Miaomiao; Luo, Qiong; Xu, Younian (Frontiers in Pharmacology, 2023)
Dexmedetomidine (DEX) is a commonly used sedative by lowering sympathetic tone and down-regulating norepinephrine (NE) levels, however, its effects on stroke-associated pneumonia (SAP), which is presumed to be brought by intensified sympathetic nervous system and consequently enhanced release of NE, remain undefined. To determine DEX's effects on SAP and investigate the underlying mechanism, we used an SAP model generated by middle cerebral artery occlusion (MCAO) and evaluated NE levels, cerebral and peripheral immunological statuses, symptoms of pneumonia, and extent of infarction. We explored in this study that despite its potential to decrease NE levels, accompanied by an increased spleen size and spleen index, DEX could neither relieve SAP symptoms nor decrease the infarct area. We investigated the peripheral and central immune state after DEX application and revealed that DEX resulted in a decrease in the CD3+ T cell population in the blood and the brain, but an increase in the CD3+ T cell population in the spleen. The detailed mechanism between decreased CD3+ T cells and DEX's role in SAP needs to be further explored. In conclusion, the clinical use of DEX in stroke patients requires careful consideration.